Lockdown stress and burnout of public health personnel during the coronavirus disease 2019 outbreak in Southern Thailand - Sopista Tunthanathip; Kasetchai Laeheem; Patchaima Buayom; Veraya Khwanthong; Chalermpol Osotpromma (Kashan University of Medical Sciences, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has affected people around the world. Therefore, this situation has caused stress and burnout among the people and public health staff in Thailand. Objective: This study aimed to compare the stress and burnout levels among public health personnel during the lockdown and un-lockdown periods of the COVID-19 pandemic in Thailand. The secondary objective was to identify the factors associated with stress and burnout. Methods: This research was a cross-sectional survey study with online self-rated questionnaires. The sample size was 158 participants. Using convenience sampling, participants who worked in 12th health region, Southern Thailand took the questionnaire twice. The first time was during May-June 2020, which was the lockdown period from the COVID-19 outbreak in Thailand, and the participants completed the questionnaires again during July-August in the same year, which was the un-lockdown period. The non-parametric sign test, Spearman's correlation, and logistic regression analyses were performed for testing the hypotheses. Results: The average total scores for stress during the lockdown and un-lockdown periods were 4.139 ± 3.534 and 3.398 ± 3.344, respectively. Moreover, the average total scores for burnout during the lockdown and un-lockdown periods were 1.573 ± 0.777 and 1.519 ± 0.702, respectively. The stress scores during the lockdown period were significantly higher than those during the un-lockdown period (sign test, P = 0.02). The stress correlated with the burnout by using Spearman's correlation (P < 0.001). Binary logistic regression showed that the stress score (odds ratio 1.75; 95% confidence interval 1.41-2.91) was a risk factor for burnout. Conclusion: During the outbreak, the stress and burnout were high; the health organizations should have interventions or activities to reduce stress and burnout.